RISIKO BENCANA DI KABUPATEN PEKALONGAN (DISASTER RISK IN PEKALONGAN REGENCY) - Ananto Aji; Wahid Akhsin Budi Nur Sidiq; Satya Budi Nugraha; Dewi Liesnoor Setyowati; Nana Kariada Tri Martuti (Universitas Negeri Semarang, 2016)
Pekalongan Regency of Central Java is a region with high risk of disaster. Various kinds of disaster such aslandslide, flood, drought, and tidal flood have somehow become “seasonal customer” for occurring inPekalongan Regency. This research aimed to prepare the mapping of disaster risk in order to strengthen theefforts in reducing disaster risk in Pekalongan Regency. The research method applied in this research refers tothe Head’s Regulation of National Risk Management Agency Number 2/2012. Since the risks of tidal flood werenot yet included in the regulation, the field observation approach was used in this research. The analysis ofdisaster risk also considered the collecting method of disaster history by organizing focus group discussion(FGD) with the related parties. The research result showed that there were high risks of flood disaster coveredsome sub-districts such as Kajen, Kesesi, Wonopringgo, Karangdadap, Tirto, Wiradesa and Wonokerto; therewere twenty six villages in total. High risk of landslide potentially occurred in large part of villages on the southarea of Pekalongan Regency. High risk of drought was relatively evenly spread in the center area. Lastly, highrisk of tidal flood potentially occurred in fifteen villages along side of Java Sea.